Risky Business: Identification, Assessment and Management of Risk Factors in Clinical Practice - ​Wendy Ashley; Aprill Baker Griffin; Allen Lipscomb (Journal of Social Work Education and Practice, 2023)
Mental health professionals manage risk in myriad of ways. A key element of effective mental health treatment is the ability to assess and manage the risks that impair client safety and impact effective treatment. However, many clinicians, whether new and seasoned, lack the skills and/or confidence to effectively identify, assess and manage risk. In this article we identify several factors that contribute to this gap, including the lack of a consistent and clear definition for risk in the literature, academic training that highlights liability with minimal to no discussion on the interpersonal dynamics inherent in risk assessment, poor or ineffective supervision and the lack of a widely accepted risk assessment and management process or tool.  Utilizing a semi-structured, 5-item survey questionnaire, practitioners (n = 75) were asked define risk and their level of comfort identifying, assessing, and stabilizing commonly presented risk factors. An analysis of participant responses reinforced that most clinicians feel they do not have adequate risk assessment and management skills or are insecure about the skills they do have. Absent from the majority of the responses were references to the relational dynamics that permeate the risk assessment process and impact how client and clinician work together to manage the risk. The findings suggest a need for both a systemic process and a comprehensive framework for clinical risk management.  Strategies and recommendations are included to guide supervisors and practitioners in navigating effective, clinically competent risk identification, assessment and stabilization.